KOMPETENSI PEGAWAI, SISTEM INFORMASI MANAJEMEN DAN KEPUASAN PESERTA - Widjanarko, Widi; Heriyanto, Meyzi; Rusli, Zaili (Jurnal Ilmu Administrasi Negara, 2019)
Employee Competency, Management Information System, Participant Satisfaction. This study aims to determine and analyze the influence of employee competencies and management information systems on the satisfaction of participants in the Social Security Service Agency (BPJS) in Pangkalan Kerinci. The study population was all participants totaling 5049 people, researchers took 100 people as samples with cluster sampling technique. Data collection methods were carried out by distributing questionnaires filled by participants. In addition, the researchers also conducted a literature review. Methods of data analysis using multiple linear regression using the help of SPSS version 18. The results showed that partially the competence of employees significantly influence participants’ satisfaction. While the management information system has a positive and significant effect on the satisfaction of BPJS participants in Pangkalan Kerinci. Simultaneously employee competencies and management information systems have a positive and significant effect on the satisfaction of BPJS participants in Pangkalan Kerinci. The coefficient of determination of employee competencies and management information systems on participant satisfaction was 77.4%. While the remaining 26.6% is an indication of other factors not examined in this study.